Effect of storage time and donor sex of transfused red blood cells on 1‐year survival in patients undergoing cardiac surgery: an observational study. Issue 5 (2nd March 2016) - Desmarets, Maxime; Bardiaux, Laurent; Benzenine, Eric; Dussaucy, Alain; Binda, Delphine; Tiberghien, Pierre; Quantin, Catherine; Monnet, Elisabeth
Abstract : BACKGROUND: Red blood cell (RBC) storage lesions and RBCs from females transfused into male recipients may have adverse effects on transfusion recipients' survival. We hypothesized that the effect of donor sex and the effect of age of blood on mortality would be most apparent in cardiac surgery patients. STUDY DESIGN AND METHODS: Using data from French Blood Services and two university hospitals, we conducted a retrospective cohort study on cardiac surgery patients whose first transfusion occurred between 2007 and 2011. The age of blood and donor sex effects on 1‐year survival were studied using Cox regression modeling, with time‐dependent stratification on the number of RBCs and adjustments for the type of surgery and other products transfused. RESULTS: Among the 2715 cardiac surgery patients, 85.1% were alive after 1 year. Age of blood and donor sex were associated with survival before adjustments (p < 0.0001). However, the adjusted hazard ratios (HRs) for patients transfused with blood stored for 29 days or more versus 14 days or less were 0.97 (95% confidence interval [95% CI], 0.69‐1.35; p = 0.98) and 1.22 (95% CI, 0.81‐1.82) for patients who received only sex‐mismatched RBCs versus all matched units (p = 0.27). For males transfused solely with female RBCs, the HR was 0.96 (95% CI, 0.57‐1.61; p = 0.69); in females transfused only with male RBCs, it was 2.03 (95% CI, 0.87‐4.73; p = 0.17). CONCLUSIONS: In this first study of survival after transfusion in France, there was no significant effect for age of blood or donor sex. Contrary to previously reported data, female RBCs appear to be safe for male recipients.